Effects of Theaflavins-rich fraction on adhesion molecules and inflammation via NF-KB pathway in stimulated Endothelial cells / Nur Hidayah Mohd Ishak - Mohd Ishak, Nur Hidayah (2015)
Theaflavins is the main polyphenolic compounds in black tea that suggested to have anti-inflammation mechanism. This study aim to determine the effects of theaflavinsrich fraction (TsRF) in Lipopolysaccharide(LPS)- stimulated Human Umbilical Vein Endothelial cells (HUVECs) on cellular adhesion molecules (CAMs; E-selectin, vascular cellular adhesion molecules;VCAM-1 and intercellular adhesion molecule; ICAM-1) and Nuclear Faktor-kappa E^NF-tcB; protein subunits p50 and p65) in both expression in gene and protein expression level. Cytotoxicity was assessed by methylthiazol- tetrazolium(MTT) assay using TsRF(Organics Herbs, China) concentrations ranging from 1.6 to 200 /xg/ml which were added to HUVECs (Cascade Biologies,USA). Confluent HUVECs were treated with LPS (Sigma,USA) and TsRF. After incubation of 16 hours, protein expression of E-selectin, VCAM-1, ICAM-1, NF- kB p50 and p65 were measured by Enzyme-linked immunosorbent assay (ELISA). Total RNA was isolated from cell pellets using the RNeasy kit (Qiagenlnc, Valencia,CA) and Gene expressions were determined by quantitative Real-Time Polymerase Chain Reaction (qPCR). TsRF <50 |xg/mL seduced viability cell to > 80%. TsRF effectively inhibited LPS-stimulated expression of E-selectin, VCAM-1 and ICAM-1 in HUVECs at the transcription level with TsRF 10-50 (ig/mL reduced of E-selectin (p<0.0001), VCAM-1 (p<0.0001), and ICAM-1 (p<0.0001). While in translation level, TsRF 10-50 |ig/mL reduced E-selectin (p<0.0001), VCAM-1 (p<0.0001), and ICAM-1 (p<0.05). Suppression of protein subunit p50 and p65 indicate that TsRF blocked the activation of NF-tcB mechanism. In gene level, TsRF 10-50 |ig/mL reduced protein subunits p65 (0.0001) and p50 (p<0.05).While expression of NF-tcB p65 (p<0.01) shown inhibition at 50 ug/ml in protein level.These results suggest that TsRF has anti-inflammatory mechanism that involves by inhibit cellular adhesion molecules expression and blocking the NF-tcB activation thus suggesting potential benefits in preventing atherosclerosis.